Improving accuracy of gaze‐control tools: Design recommendations for optimum position, sizes, and spacing of interactive objects - Niu, Ya‐feng; Zuo, Hong‐rui; Yang, Xin; Xue, Cheng‐qi; Peng, Ning‐yue; Zhou, Lei; Zhou, Xiao‐zhou; Jin, Tao (Human factors and ergonomics in manufacturing & service industries, 2021)
To investigate a suitable design of interactive objects in the fixation‐triggered eye‐control interface, this study conducted two ergonomic experiments based on the location of an object, area of the object, and distance between adjacent objects. Experiment 1 investigated the priority distribution of different regions and recommended values of object sizes in different regions. The results showed that middle‐middle (MM) area is the optimal area, while middle‐left (ML) area, middle‐right (MR) area, and upper‐left (UL) area are suboptimal areas, and the remaining are general areas. The recommended minimum sizes for the optimal area, suboptimal area, and general area are 2.636° (200 px on the screen of a 1920 px × 1080 px 14 inch monitor), 2.978° (225 px on the screen of a 1920 px × 1080 px 14 inch monitor) and 3.322° (250 px on the screen of a 1920 px × 1080 px 14‐inch monitor), respectively. Experiment 2 conducted ergonomic experiments of different distances between adjacent objects in horizontal and vertical distributions. The results showed that the appropriate setting of the distribution and size of the objects showed no significant difference between different levels of spacing on the trigger accuracy rate and task completion time. Further, 1.032° (75 px on the screen of a 1920 px × 1080 px 14‐inch monitor) could be recommended as the most suitable spacing. According to the conclusions of Experiments 1 and 2, an optimized eye‐control interface and the NASA‐TLX scale were used to verify the validity and scientificity of the experimental results. The conclusions can be employed to improve the interaction efficiency of the eye‐control system and user experience and expand the application field of eye control.